Production of Propene from n‐Butanol: A Three‐Step Cascade Utilizing the Cytochrome P450 Fatty Acid Decarboxylase OleTJE. (5th August 2020) - Bauer, Daniel; Zachos, Ioannis; Sieber, Volker
Abstract: Propene is one of the most important starting materials in the chemical industry. Herein, we report an enzymatic cascade reaction for the biocatalytic production of propene starting from n ‐butanol, thus offering a biobased production from glucose. In order to create an efficient system, we faced the issue of an optimal cofactor supply for the fatty acid decarboxylase OleT JE, which is said to be driven by either NAD(P)H or H2 O2 . In the first system, we used an alcohol and aldehyde dehydrogenase coupled to OleT JE by the electron‐transfer complex putidaredoxin reductase/putidaredoxin, allowing regeneration of the NAD + cofactor. With the second system, we intended full oxidation of n ‐butanol to butyric acid, generating one equivalent of H2 O2 that can be used for the oxidative decarboxylation. As the optimal substrate is a long‐chain fatty acid, we also tried to create an improved variant for the decarboxylation of butyric acid by using rational protein design. Within a mutational study with 57 designed mutants, we generated the mutant OleTV292I, which showed a 2.4‐fold improvement in propene production in our H2 O2 ‐driven cascade system and reached total turnover numbers >1000. Abstract : Propelled to propene : Propene is produced in a three‐step enzymatic cascade from n ‐butanol via butanal and butyric acid, with the last step being oxidative decarboxylation catalyzed by OleT JE . Variation of the supply of redox donors demonstrates the peroxygenase nature of OleT JE . A mutational study led to a new variant, OleTV292I, which shows significantly higher activity towards the short‐chain substrate.